PEMBEKALAN KARYAWAN KLINIK GRAND MEDICA INDONESIA AKAN PENTINGNYA MUTU PELAYANAN - yuliana, lina; Zulfikar, Iwan; Noeryanto; Fuadi, Yan; Ramdan, Muhamad (Program Studi D4 K3 Universitas Balikpapan, 2023)
Quality of Health Services According to Edward Deming (1940), Quality is a service that can satisfy customers, According to Joseph M. Juran (1954), that quality is the suitability of product use to meet customer satisfaction. Meanwhile, according to Supriyanto & Wulandari (2011), quality is the overall characteristics and description of goods or services that show their ability to satisfy customer needs. So that it can be said that quality is something that is used to guarantee the expected goals or outcomes and quality must always keep up with the latest developments in professional knowledge in order to satisfy customers. The importance of education and training is not only beneficial for the employees or employees concerned, but also benefits for the organization. Because with increased productivity or skills of employees, increase work productivity of employees. Employee work productivity increases, meaning the organization concerned will benefit.